Evaluation of the Medical Care of Patients with Hypertension in an Emergency Department and in Ambulatory Hypertension Unit - Nobre,Fernando (2002)
OBJECTIVE: To evaluate the characteristics of the patients receiving medical care in the Ambulatory of Hypertension of the Emergency Department, Division of Cardiology, and in the Emergency Unit of the Clinical Hospital of the Ribeirão Preto Medical School. METHODS: Using a protocol, we compared the care of the same hypertensive patients in on different occasions in the 2 different places. The characteristics of 62 patients, 29 men with a mean age of 57 years, were analyzed between January 1996 and December 1997. RESULTS: The care of these patients resulted in different medical treatment regardless of their clinical features and blood pressure levels. Thus, in the Emergency Unit, 97% presented with symptoms, and 64.5% received medication to rapidly reduce blood pressure. In 50% of the cases, nifedipine SL was the elected medication. Patients who applied to the Ambulatory of Hypertension presenting with similar features, or, in some cases, presenting with similar clinically higher levels of blood pressure, were not prescribed medication for a rapid reduction of blood pressure at any of the appointments. CONCLUSION: The therapeutic approach to patients with high blood pressure levels, symptomatic or asymptomatic, was dependent on the place of treatment. In the Emergency Unit, the conduct was, in the majority of cases, to decrease blood pressure immediately, whereas in the Ambulatory of Hypertension, the same levels of blood pressure, in the same individuals, resulted in therapeutic adjustment with nonpharmacological management. These results show the need to reconsider the concept of hypertensive crises and their therapeutical implications.